Self-Intention in Mediating Self-Competence and Memorization Methods on Intensity of Memorizing the Qur'an: PLS-SEM Approach - Kamila, Lia Alfi; Mahmudin, Afif Syaiful; Daryono, Rihab Wit (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
Considering the various factors faced by students in the Tahfidz program, this research aimed to explore the role of self-intention as a mediator in the influence between self-competence, memorization methods, and the intensity of memorizing the Qur'an. This research used a quantitative approach with a survey research method to collect data based on purposive sampling with 45 out of 50 students in the tahfidz program at Pondok Pesantren Tahfidzul Qur'an Al-Hasan Ponorogo. Data collection was carried out using a questionnaire consisting of a Likert scale with four alternative answers. PLS-SEM analysis was used to analyze the data and test the conceptual model. The results of the analysis showed that self-competence and self-intention had no significant effect on the intensity of memorizing the Qur'an. However, this finding has practical implications, as it highlights the importance of self-intention in increasing the intensity of memorizing the Qur'an through self-competence and memorization methods. This underscores the need for setting clear goals and increasing motivation to instill an attitude of never giving up and trying to achieve memorization targets. Consistency and discipline are the primary keys to increasing the intensity of memorizing the Qur'an. In addition to self-competence and memorization methods, other factors can affect the intensity of memorizing the Qur'an, such as motivation, social support, and learning environment.